Clean shrimps after all - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
After a boom decade in the 1980s, world production of cultivated shrimp has fallen sharply due to intensive and polluting methods of cultivation, which encourage diseases (see Spore 82, page 4 & 5). Some say it would be best to stop such methods....